Transformation of Inclusive Education Services: A Case Study in Primary Schools - Khotimah, Khusnul; Widhyanti, Nugraheni Dwi; Widyasari, Choiriyah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the transformation of inclusive education services in elementary schools by examining service profiles, learning interactions, innovative strategies, and the challenges arising during implementation. A qualitative approach with a case study design was employed to gain a profound understanding of inclusive education practices in schools. Data were collected through semi-structured interviews with principals, teachers, and students, participant observation in classrooms, and documentation of instructional materials and school records. Data analysis was conducted using thematic analysis through the stages of data reduction, data display, and conclusion drawing, with source triangulation to ensure validity. The results indicate that inclusive education services have undergone adaptive and collaborative transformations. Schools demonstrate a commitment to providing equitable learning opportunities, while teachers effectively adapt instructional methods to meet students' needs through verbal, visual, and kinesthetic approaches. Peer interactions have developed positively through mutual assistance, empathy, tolerance, and cooperation. Innovative learning strategies, such as educational games, group discussions, and collaborative activities, have proven effective in increasing student motivation and engagement. Despite obstacles such as limited facilities, diverse student abilities, and time constraints, schools and teachers have managed these challenges through schedule adjustments, creative media utilization, and individualized mentoring. This transformation supports the creation of a more equitable, inclusive, and sustainable learning environment.